ARSITEKTUR INTEGRASI APLIKASI E-GOV. DI INDONESIA - Candra Taufik (POLITEKNIK PIKSI GANESHA, 2018)
Decentralization gives authority to agencies / institutions / organizations in each province to plan the creation and development of applications tailored to their needs. Data related to the development is stored in each application of the organization which is periodically reported to the respective leader of government. The development data is very necessary for decision making in the next period development planning. Transparency and accountability are the absolute requirements for reporting development data, for that it is necessary to increase the speed and accuracy of data collection, so that progress in regional development can be monitored continuously and decision making can be carried out more quickly. Therefore, it is necessary to integrate applications from all applications found in agencies / institutions / organizations in each province.This research is aimed at studying alternative E-Gov application integration architecture that could be implemented in several government agencies / institutions / organizations. Qualitative methods are used in this study, namely by studying some related literatures to obtain alternative architectures.With the existence of an alternative integration architectures, it is expected to facilitate the design of application integration in more detail.